Internalization Of Religious-Pancasilaist Character Through Anti-Corruption Education - Tripuspita, Neneng (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze efforts to internalize the Pancasila-religious character through anti-corruption education. This research uses a qualitative approach with the method of literature study. Data sources are taken from credible websites, including Sinta and Google Scholar. The results of this research show that corrupt acts are behavior that deviates from the religion and ideology of Pancasila which is triggered by money-based political issues, weak legislation and sanctions for corruptors, feudalistic views and the luxurious life of state officials, bureaucratic systems and administration that provide loopholes for corrupt behavior, abuse of authority, and the legacy of Dutch colonialism. For this reason, anti-corruption education is needed with the main aim of creating good governance as a form of good, clean and dignified government. The characteristics of good governance are participation of all parties, law-based, transparency, responsiveness, consensus orientation, equality, effectiveness and efficiency, and accountability. Apart from that, special treatment is needed for corruptors, namely deterrent punishments such as taking over all their assets from the state and